An Overview on Nocardiopsis Species Originating From North African Biotopes as a Promising Source of Bioactive Compounds and In Silico Genome Mining Analysis of Three Sequenced Genomes - (:unkn) unknown (My University, 2024)
Actinobacteria are renowned for their prolific production of diverse bioactive secondary metabolites. In recent years, there has been an increasing focus on exploring “rare” genera within this phylum for biodiscovery purposes, notably the Nocardiopsis genus, which will be the subject of the present study. Recognizing the absence of articles describing the research process of finding bioactive molecules from the genus Nocardiopsis in North African environments. We, therefore, present a historical overview of the discoveries of bioactive molecules of the genus Nocardiopsis originating from the region, highlighting their biological activities and associated reported molecules, providing a snapshot of the current state of the field, and offering insights into future opportunities and challenges for drug discovery. Additionally, we present a genome mining analysis of three genomes deposited in public databases that have been reported to be bioactive. A total of 36 biosynthetic gene clusters (BGCs) were identified, including those known to encode bioactive molecules. Notably, a substantial portion of the BGCs showed little to no similarity to those previously described, suggesting the possibility that the analyzed strains could be potential producers of new compounds. Further research on these genomes is essential to fully uncovering their biotechnological potential. Moving forward, we discuss the experimental designs adopted in the reported studies, as well as new avenues to guide the exploration of the Nocardiopsis genus in North Africa.
Keywords: African Research